Chas izbiratelia . Chas izbiratelia . The Electorate's Hour . Час избирателя - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A program on the election campaign: presentations by representatives of various blocs. Featured in the program: Ziuganov, Gennadii Andreevich (Politician) Contributors: Berdnikova, Nina (Anchor) Передача в рамках избирательной кампании: выступления представителей различных блоков. В программе участвуют: Зюганов, Геннадий Андреевич (Политик) Создатели: Бердникова, Нина (Ведущий/Ведущая)